Conflict between the State and Indigenous Communities: A Study of the Construction of a Naval Military Base in the Aru Islands Regency 1991-2021 - Gaston Otto Malindir (Political Sciences Program Study, 2025)
The purpose of this study is to analyze and describe the conflict between the state and indigenous communities in the case of the construction of a naval military base in Marfenfen Village, Aru Islands Regency, Maluku Province from 1991 to 2021. This study uses a qualitative method with data collection through literature studies. The analytical techniques used are data reduction, data presentation, and drawing conclusions. The results show that the Marafenfen conflict reflects structural tensions between the state and indigenous communities in the struggle for living space. The customary land dispute with the Indonesian National Armed Forces (TNI) demonstrates weak legal protection, manipulative bureaucratic practices, and judicial bias that emphasizes formal legality over substantive justice. When state law fails, indigenous communities actualize resistance through mass action and sasi, asserting their position as a political force based on local wisdom that is able to delay the state's agenda from 1991 to 2021.